Ludzkie zoo w percepcji dzieci - Tomasz Nowicki (Problemy Wczesnej Edukacji)
The presented article explores the idea of the Human Zoo and the children’s perception of the possibility of keeping people in the Zoo. From the point of view of analytical practice, the collected statements of children were examined by means of a critical discourse analysis understood by Fairclough as textual and linguistic social practices reflecting the symbolic structure. The children’s statements show unequivocal resistance to the vision of exposure of the human body and strong species identification. The images of the Human Zoo make it possible to see the orientation to the perception of the species relationship in the normative dimension. This orientation takes place on an emotional level, confirming research in the field of moral development and the concept of emotivism. The reversal of order, in turn, shows the social order as a brutal genre struggle, activating the imaginary of nature perceived as threatening and dangerous.